Encouraging Environmental Stewardship Among Business Students: A Design Thinking Exploration - Billy Purwocaroko Noeringtyas; Mima Kurniasih (Center for Risk Management & Sustainability and RSF Press, 2025)
This study addresses a critical gap in business education where traditional methods often fail to translate theoretical knowledge of sustainability into a deep, action-oriented commitment to environmental stewardship. The WEF Report on Jobs of the Future 2025 highlights the urgent need for a workforce equipped with green skills, yet business students frequently lack the practical tools to integrate environmental responsibility into their professional lives. This paper explores the Design Thinking framework as an innovative pedagogical tool to bridge this divide. Employing a qualitative action research design, we engaged a cohort of business students in a hands-on Design Thinking intervention. Data collected through observations, participant feedback, and prototype ideas generated by participants. The findings demonstrate that Design Thinking(DT) is a highly effective methodology for cultivating a tangible sense of stewardship and developing the critical skills demanded by the future economy. This empathy-driven process leads to changes in students' perceptions and attitudes, directly fostering the core competencies needed for green skills. The structured process empowered students to move from passive learning to proactive problem-solving, resulting in the development of creative and actionable prototypes for real-world environmental challenges. This research offers a practical model for business schools seeking to integrate sustainability more meaningfully into their curricula. While the study's scope is limited to a single group, it provides a strong foundation for future research into experiential learning methods that cultivate responsible business leaders.